Short-term statistical analysis of the occurrence of the F3 layer in Malaysian ionosphere for winter 2004 - Jaafar, Mohd Kamal (2005)
The ionospheric ionogram is observed in the equatorial zone located at Parit Raja, Daerah Batu Pahat, Johor, Malaysia (Latitude: 1 ° 86 ' North, and Longitude: 103 " 08 ' East) for the winter months of December 2004, January and February 2005 continuously. A Vertical Digital Sounder is used to measure and to determine the critical frequency, virtual height, MUF and electron density at any given time. Daily data is collected from 1s t December 2004 to 28lb February 2005. The main work is to investigate the presence of the F3 layer. A statistical analysis of the occurrence of the F3 layer recorded at the equatorial station Parit Raja is also presented. The greatest occurrence of the F3 layer is in the period between 1100 LT to 1300 LT (0300 -0500 UTC) due to ion density being maximum at noon. Between 0700 LT to 0900 LT (2300 - 0200 UTC) the occurrence is the least due to ion density being minimum just after sunrise. The mean critical frequency for the F3 layer is about 8 MHz (f0F3) and for the F2 layer is about 6 MHz (foF2 ), while the mean virtual height for F3 layer is about 600 km (h'F3) and 300 km (h'F2) for F2 layer. The maximum virtual height of the F3 layer (h'F3) recorded is about 900 km on the 7t h February 2005 at 1800 LT (1000 UTC) while the minimum is about 420 km on the 5t h February 2005 at 1300 LT (0500 UTC). The maximum virtual height of the F2 layer (h'F2) recorded is about 470 km on the 14th December 2004 at 2030 LT (1230 UTC) while the minimum is about 200 km on the 30th December 2004 at 1230 LT (0430 UTC). The Kp (0 - 4) index is below geomagnetic storm level and it is suitable for HF propagation for equatorial station. Further observation and investigation is required to understand the occurrence of the F3 layer.